J/[psi] production as a function of charged particle multiplicity in pp collisions at √s=7 TeV* - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Krawutschke, Tobias; Kweon, MinJung; Lohner, Daniel; Lu, Xianguo; Mercado Pérez, Jorge; Oyama, Ken; et al. (Physics letters, 2012)
The ALICE Collaboration reports the measurement of the relative J/ψ yield as a function of charged particle pseudorapidity density dNch/dη in pp collisions at s=7 TeV at the LHC. J/ψ particles are detected for pt>0, in the rapidity interval |y|<0.9 via decay into e+e−, and in the interval 2.5<y<4.0 via decay into μ+μ− pairs. An approximately linear increase of the J/ψ yields normalized to their event average (dNJ/ψ/dy)/〈dNJ/ψ/dy〉 with (dNch/dη)/〈dNch/dη〉 is observed in both rapidity ranges, where dNch/dη is measured within |η|<1 and pt>0. In the highest multiplicity interval with 〈dNch/dη(bin)〉=24.1, corresponding to four times the minimum bias multiplicity density, an enhancement relative to the minimum bias J/ψ yield by a factor of about 5 at 2.5<y<4 (8 at |y|<0.9) is observed.
Im Titel wird "psi" als griechischer Buchstabe dargestellt
ALICE Collaboration: B. Abelev, V. Anguelov, O. Busch, P. Glässel, R.Grajcarek, N. Herrmann, T. Krawutschke, M.J. Kweon, D. Lohner, X. Lu, J. Mercado Pérez, K. Oyama, Y. Pachmayer, S. Radomski, K. Reygers, R. Schicker, K. Schweda, J. Stachel, J. Ulrich, S. Vallero, Y. Wang, J. Wiechula, A. Zimmermann [und weitere]
Gesehen am 30.11.2018